The mitochondrial genome of the ethanol-metabolizing, wine cellar mold Zasmidium cellare is the smallest for a filamentous ascomycete - Goodwin, Stephen B.; McCorison, Cassandra B.; Cavaletto, Jessica R.; Culley, David E.; LaButti, Kurt; Baker, Scott E.; Grigoriev, Igor V. (Fungal biology, 2016)
Fungi in the class Dothideomycetes often live in extreme environments or have unusual physiology. One of these, the wine cellar mold Zasmidium cellare, produces thick curtains of mycelia in cellars with high humidity, and its ability to metabolize volatile organic compounds is thought to improve air quality. Whether these abilities have affected its mitochondrial genome is not known. To fill this gap, the circular-mapping mitochondrial genome of Z. cellare was sequenced and, at only 23 743 bp, is the smallest reported for a filamentous fungus. Genes were encoded on both strands with a single change of direction, different from most other fungi but consistent with the Dothideomycetes. Other than its small size, the only unusual feature of the Z. cellare mitochondrial genome was two copies of a 110-bp sequence that were duplicated, inverted and separated by approximately 1 kb. This inverted-repeat sequence confused the assembly program but appears to have no functional significance. The small size of the Z. cellare mitochondrial genome was due to slightly smaller genes, lack of introns and non-essential genes, reduced intergenic spacers and very few ORFs relative to other fungi rather than a loss of essential genes. Whether this reduction facilitates its unusual biology remains unknown. [Display omitted] •The Zasmidium cellare mitochondrial genome is the smallest among filamentous fungi.•Reduced genome size was not due to loss of genes for aerobic respiration.•Gene order in fungal mitochondrial genomes is completely scrambled.•Phylogenetic analysis confirms a likely placement of Z. cellare in the Capnodiales.•Inverted repeats can confuse assembly programs.